Pathological alterations in goats intravenously infected with Aspergillus fumigatus - Gupta, P P; Mandal, P C (The Indian Journal of Animal Sciences, 2012)
Intravenous inoculation of goats with Aspergillus fumigatus spores resulted in the development of generalized aspergillosis. Lesions were consistently seen in the lungs, kidneys and heart and occasionally in the liver, spleen, abomasum and mediastinal lymphnodes. The experiment was continued for 11 days. Gross changes included congestion, oedema and haemorrhages in the first 3 days followed by the development of greyish-white nodules in the lungs, heart and kidneys. Microscopic changes consisted of necrotic foci, abseesses and thrombosis of the blood vessels invaded by the hyphae of A. funigatus. By 9 day after infection, the lesions in the lungs became granulomatous. The fungus was consistently isolated from the lesions in lungs, kidneys and heart up to 11 days. An increase in total immunoglobulins in serum was also recorded.